ANALYSIS OF THE LERNER INDEX OF THE HALAL FOOD INDUSTRY IN BANGKA BELITUNG FROM THE PERSPECTIVE OF IBN KHALDUN'S PRICE CONCEPT - Fitriyanti, Eka; Wulandari, Ayu; Fahria, Izma; Karimullah, Suud Sarim (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2025)
The halal food industry in Bangka Belitung is a rapidly growing sector in line with the increasing awareness of Muslim consumers about the importance of halal products. This study aims to analyze the market power of halal food companies in the province using the Lerner Index, and to relate it to the price concept proposed by Ibn Khaldun. The method used is a quantitative approach by calculating the Lerner Index based on price and marginal cost data from 173 halal food companies. The research results show a variation in market power, where some companies have the ability to set prices above marginal cost, while others operate in a more competitive market. In Ibn Khaldun's perspective, excessively high prices due to market power can create injustice in the accessibility of halal products. These findings underscore the importance of policies that support healthy competition and fair pricing, to create a more equitable halal market in Bangka Belitung